Signaling Pathways That Regulate the Enhanced Disease Resistance of Arabidopsis “Defense, No Death” Mutants - Ruth K. Genger; Grace I. Jurkowski; John M. McDowell; Hua Lu; Ho Won Jung; Jean T. Greenberg; Andrew F. Bent (Molecular Plant-Microbe Interactions, 2008)
Arabidopsis dnd1 and dnd2 mutants lack cyclic nucleotide-gated ion channel proteins and carry out avirulence or resistance gene–mediated defense with a greatly reduced hypersensitive response (HR). They also exhibit elevated broad-spectrum disease resistance and constitutively elevated salicylic acid (SA) levels. We examined the contributions of NPR1, SID2 (EDS16), NDR1, and EIN2 to dnd phenotypes. Mutations that affect SA accumulation or signaling (sid2, npr1, and ndr1) abolished the enhanced resistance of dnd mutants against Pseudomonas syringae pv. tomato and Hyaloperonospora parasitica but not Botrytis cinerea. When SA-associated pathways were disrupted, the constitutive activation of NPR1-dependent and NPR1-independent and SA-dependent pathways was redirected toward PDF1.2-associated pathways. This PDF1.2 overexpression was downregulated after infection by P. syringae. Disruption of ethylene signaling abolished the enhanced resistance to B. cinerea but not P. syringae or H. parasitica. However, loss of NPR1, SID2, NDR1, or EIN2 did not detectably alter the reduced HR in dnd mutants. The susceptibility of dnd ein2 plants to B. cinerea despite their reduced-HR phenotype suggests that cell death repression is not the primary cause of dnd resistance to necrotrophic pathogens. The partial restoration of resistance to B. cinerea in dnd1 npr1 ein2 triple mutants indicated that this resistance is not entirely EIN2 dependent. The above findings indicate that the broad-spectrum resistance of dnd mutants occurs due to activation or sensitization of multiple defense pathways, yet none of the investigated pathways are required for the reduced-HR phenotype.